Policy incoherence in smallholder dairying in Bihar, India - Sulaiman, R.V.; Vamsidhar Reddy, T.S. (International Livestock Research Institute, 2015)
Small holder dairying plays an important role in the socioeconomic development of Bihar. While several organizations exist for dairy development in Bihar and there is an increase in investments and interventions in this sector during the last one decade, these are yet to contribute to increasing milk productivity. The paper maps the existing innovation capacity of the small holder dairy sector through an analysis of patterns of interaction among the various actors and identifies the major institutions and policies that currently constrain development of improved capacity for innovation. The paper argues the need for addressing the policy incoherence in the small holder dairy sector in Bihar through organization of a multi-stakeholder policy working group which focuses on ways of addressing policy gaps, enhances capacities for policy implementation and facilitates policy learning.